The cytotoxicity of silver nanoparticles on human gingival fibroblast cells: An in vitro study - Putthanuparp, Thanapha; Rirattanapong, Praphasri; Ruangsawasdi, Nisarat (Mahidol Dental Journal, 2023)
Objective: The aim of this study was to evaluate the toxic effects of silver nanoparticles (AgNPs) on human gingival fibroblast (HGF) cells at different concentrations and treatment durations. Methods and Material: AgNPs were synthesized via the chemical reduction of silver nitrate with sodium borohydride in a chitosan solution at the Pharmacology Department, Faculty of Dentistry, Mahidol University, Thailand. HGF cells were exposed to 0.5, 1.5, 2.5, 5, or 10 μg/mL AgNPs for 2 min and 24 h. The positive control was 0.12% Chlorhexidine, while the negative control was growth medium. Cell viability was determined using a Methylthiazol tetrazolium bromide assay, and images were obtained using a light microscope. The uptake of 0.5 mg/ml AgNPs by HGF cells after a 24-h incubation was observed using transmission electron microscopy (TEM). Results: A 2-min exposure to 0.5−10 μg/mL AgNPs did not induce cytotoxicity. In contrast, a 24-h exposure led to a significant decrease in cell viability, however, it remained above 70% compared with the control. Exposure to AgNPs for 24 h resulted in a lower density of HGF cells and more degenerative cells when the concentration of AgNPs increased observed with the microscope. TEM analysis revealed the absorption, internalization, and dissemination of 0.5 μg/mL AgNPs in HGF cells after a 24-h incubation. Conclusions: The cytotoxicity of AgNPs was concentration- and exposure time-dependant, as evidenced by the intracellular accumulation observed using TEM after a 24-h exposure. Concentrations below 10 μg/mL can be considered non-cytotoxic during short-term oral cavity exposure. Based on our results, the use of AgNPs in dentistry is likely to be safe for oral application.